SIKAP SATYA DAN BAKTI DALAM GEGURITAN PANCA DATU (WIT WASTAN JAGAT BALI) - Putera Semadi, Anak Agung Gde (Widya Accarya, 2018)
Abstract          Geguritan Panca Datu (Wit Wastan Jagat Bali) is a traditional Balinese literature work which uses macepat song as it literary media. Bali is historical values and satya bakti philosophy which are developed as the main theme in this work can be utilized to guide polite character for each generation. This problem is very interesting to be studied from the paradigm of literature psychology theory. This study is a type of qualitative research. The data were collected by using library study method and assisted with in-depth interview techniques, participatory observation, note, and recording. All data were reviewed by both analysis descriptive method and text content analysis. The presentation of that data analysis result is delivered verbally, sharply, and systematically. Satya and bakti are two powerful mental attitudes which can be applied in reaching the success of life goals and this life which are based on dharma. In Geguritan Panca Datu (Wit Wastan Jagat Bali) these two forms of attitude are purely highlighted as the embodiment of truly value-field work of art.                                                                                       Key words :  Geguritan, Satya, and Bakti. AbstrakGeguritan Panca Datu (Wit Wastan Jagat Bali) adalah karya sastra Bali tradisional yang menggunakan tembang macepat sebagai medium sastranya. Nilai-nilai historis Bali dan filosopis satya bakti yang dikembangkan sebagai tema utama dalam karya ini dapat dimanfaatkan untuk menuntun karakter yang santun bagi setiap generasi. Permasalahan ini sangat menarik dikaji dari paradigma teori psikologi sastra.Penelitian ini termasuk jenis penelitian kualitatif. Data yang dikumpulkan menggunakan metode studi pustaka dan dibantu dengan teknik wawancara mendalam, observasi partisipasi, pencatatan, dan rekaman. Seluruh data dikaji dengan metode deskriptif analisis serta analisis isi teks. Penyajian hasil analisis data itu dilakukan secara verbal, tajam, dan sistematis.Satya dan bakti adalah dua sikap batin yang sangat kuat dapat diaplikasikan dalam mencapai kesuksesan tujuan hidup dan kehidupan ini berdasarkan atas dharma. Dalam Geguritan Panca Datu (Wit Wastan Jagat Bali) kedua bentuk sikap tersebut murni ditonjolkan sebagai  perwujudan karya seni yang benar-benar sarat nilai. Kata kunci : Geguritan, Satya, dan Bakti.